Positive 'whānau management' : privileging the centrality of whānau and culturally specific understandings of child discipline for effective psychological practice with Māori : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Poananga, Sara Maraea (Massey University, 2011)
The passing of the ‘anti-smacking’ law in 2007 took the practice of child discipline to the forefront of public debate in Aotearoa, New Zealand. Questions emerged concerning effective alternative forms of discipline to physical punishment. While there is a great deal of psychological knowledge on discipline, there is a dearth of research that specifically examines Māori child-rearing and discipline practices. This is important knowledge for psychologists to have, considering their role in the prevention of child abuse and their ethical obligation to promote positive discipline strategies. As children of Māori ethnicity are currently over-represented in child abuse statistics, it is particularly important that psychologists acquire the awareness, knowledge and skills needed to work competently with Māori when addressing issues of child discipline. In spite of these negative statistics, this thesis promotes a strength-based approach to working and researching with Māori and aimed to explore the successful Māori child-rearing values and practices in operation today, and how these behavioural discipline strategies can be effective in psychological practice with Māori. Adopting a ‘Māori research paradigm’, which incorporated both Māori-centred and Kaupapa Māori research principles, in-depth semi-structured interviews were employed to determine how Māori psychologists, as experts of best practice for Māori, negotiated psychological practices when addressing discipline. This was combined with a case study of a contemporary Māori whānau operating in strength with the use of a positive non-smacking approach to ‘whānau management’. Thematic analyses of the data led this thesis to conclude that privileging the centrality of whānau and culturally specific understandings of child-rearing and discipline is necessary for effective psychological practices that draw on standard behavioural discipline strategies. This thesis then addressed the ways in which these understandings are relevant to New Zealand psychologists’ ethical obligation to cultural competencies.
Keywords: Child discipline; Maori child-rearing